2023
DOI: 10.3390/foods12102053
|View full text |Cite
|
Sign up to set email alerts
|

Piper nigrum Extract: Dietary Supplement for Reducing Mammary Tumor Incidence and Chemotherapy-Induced Toxicity

Nadeeya Mad-adam,
Siribhon Madla,
Narissara Lailerd
et al.

Abstract: A low piperine fractional Piper nigrum extract (PFPE) was prepared by mixing cold-pressed coconut oil and honey in distilled water, namely, PFPE-CH. In this study, PFPE-CH was orally administered as a dietary supplement to decrease the risk of tumor formation and reduce the side effects of chemotherapeutic drugs during breast cancer treatment. The toxicity study demonstrated no mortality or adverse effects after administrating PFPE-CH at 5000 mg/kg during a 14-day observation period. Additionally, PFPE-CH at 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…In this study, we performed approximately 3 months animal testing to evaluate the effect of PFPE on preventing breast cancer and modulating immune cells in blood circulation for future use in clinical trials. Our study used MCT oil instead of coconut oil that was used in previous study [15] for better solubility as MCT oil contains only medium chains while coconut contains medium and long-chain fat [17]. Vit E is an antioxidant that is used to prevent oil rancidity instead of honey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we performed approximately 3 months animal testing to evaluate the effect of PFPE on preventing breast cancer and modulating immune cells in blood circulation for future use in clinical trials. Our study used MCT oil instead of coconut oil that was used in previous study [15] for better solubility as MCT oil contains only medium chains while coconut contains medium and long-chain fat [17]. Vit E is an antioxidant that is used to prevent oil rancidity instead of honey.…”
Section: Discussionmentioning
confidence: 99%
“…Combining PFPE with the chemotherapy drug (doxorubicin) improves blood parameters and reduces pro-tumorigenic cytokine induced by doxorubicin [14]. A recent study reported that PFPE reduces mammary tumor incidence and chemotherapy-induced toxicity [15].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that PFPE-CH, a dietary supplement made by mixing a low piperine fractional Piper nigrum extract (PFPE) with cold-pressed coconut oil and honey in distilled water, can help decrease the risk of tumor formation and reduce the side effects of chemotherapeutic drugs during breast cancer treatment. This is promising news for those undergoing treatment for breast cancer [ 13 ]. In the early 1970s, a piperine analogue Ilepcimide was originally extracted from a Chinese folk remedy, which was discovered as a safe and effective antiepileptic drug through structural characterization.…”
Section: Introductionmentioning
confidence: 99%